Out there : the science behind sci-fi film and TV - Waldman, Ariel (Running Press, 2023)
"Explore the science behind some of your favorite popular science fiction tropes--from escaping a black hole to riding a space elevator to the stars--in this illustrated guide from NASA advisor and host of the popular Tested podcast Offworld"--